Bacterial Transcriptional Control Methods and Protocols - Artsimovitch, Irina; Santangelo, Thomas J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume is designed to be a resource of proven techniques and approaches for probing the activities of bacterial, eukaryotic, and archaeal RNA polymerases. This book features a collection of in vitro and in vivo technologies that will permit researchers to purify and probe the position and stability of RNA polymerase complexes at different points of the transcription cycle, analyze the various translocations and intermolecular movements associated with catalysis, define recruitment strategies, probe the roles of transcription factors in each stage of the cycle, highlight conserved and disparate fidelity mechanisms, analyze the resultant transcripts, and study coordination of the nascent mRNA synthesis by the RNA polymerase and mRNA translation by the ribosome. Written in the highly successful Methods of Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubles troubleshooting and avoiding known pitfalls. Practical and timely, Bacterial Transcriptional Controls: Methods and Protocols highlights the breadth and depth of techniques that are likely to continue shaping the transcription community in the future.
Mapping the Escherichia coli Transcription Elongation Complex with Exonuclease III -- Purification of Bacterial RNA Polymerase: Tools and Protocols -- Monitoring Translocation of Multisubunit RNA Polymerase Along the DNA with Fluorescent Base Analogues -- In vitro and in vivo Methodologies for Studying the Sigma54-dependent Transcription -- Methods for the Assembly and Analysis of in vitro Transcription-coupled-to-translation Systems -- Site-specific Incorporation of Probes into RNA Polymerase by Unnatural-amino-acid Mutagenesis and Staudinger-Bertozzi Ligation -- Reconstitution of Factor-dependent, Promoter Proximal Pausing in Drosophila Nuclear Extracts -- Direct Competition Assay for Transcription Fidelity -- Single-stranded DNA Aptamers for Functional Probing of Bacterial RNA Polymerase -- Biochemical Analysis of Transcription Termination by RNA Polymerase III from Yeast Saccharomyces cerevisiae -- Use of RNA Polymerase Molecular Beacon Assay to Measure RNA Polymerase Interactions with Model Promoter Fragments -- Preparation of cDNA Libraries for High-throughput RNA Sequencing Analysis of RNA 5’ Ends -- In situ Footprinting of E. coli Transcription Elongation Complex with Chloroacetaldehyde -- Using Solutes and Kinetics to Probe Large Conformational Changes in the Steps of Transcription Initiation -- Manipulating Archaeal Systems to Permit Analyses of Transcription Elongation-termination Decisions in vitro -- Purification of Active RNA Polymerase I from Yeast -- Transcription in Archaea: preparation of Methanocaldococcus jannaschii Transcription Machinery -- Transcription in Archaea: in vitro Transcription Assays for mjRNAP -- Experimental Analysis of hFACT Action during Pol II Transcription in vitro -- ChIP-seq for Genome-scale Analysis of Bacterial DNA-binding Proteins.
Keywords: Microbiology; Bacteriology; Genetic engineering; Microbiology; Bacteriology; Genetic Engineering